Circulating MicroRNAs as Quantitative Biomarkers for Diagnosis and Prognosis of Uveal Melanoma - Zhou, Wen-Da; Shao, Lei; Dong, Li; Zhang, Rui-Heng; Li, Yi-Fan; Li, He-Yan; Wu, Hao-Tian; Shi, Xu-Han; Wei, Wen-Bin (Frontiers in Oncology, 2022)
For uveal melanoma (UM) patients, it is significant to establish diagnosis and prognosis evaluation systems through imaging techniques. However, imaging examinations are short of quantitative biomarkers and it is difficult to finish early diagnosis of UM. In order to discover new molecular biomarkers for the diagnosis and prognostic evaluation of UM, six circulating miRNAs (mir-132-3p, mir-21-5p, mir-34a-5p, mir-126-3p, mir-199a-3p, mir-214-3p) were chosen as candidates for independent validation. Validation of these miRNAs was performed in a cohort of 20 patients, including 10 spindle shaped melanoma and 10 epithelioid cell melanoma, and 10 healthy donors. Then 5 patients with metastatic UM were included to validate the performance of miRNAs in advanced UM. Serum levels of miRNAs were determined using quantitative real-time PCR. We confirmed significantly higher levels of three miRNA in serum of UM patients in comparison to healthy controls, and miR-199a-3p had the best performance (P<0.0001; AUC=0.985). MiR-214-3p and miR-21-5p were significantly up-regulated in serum of epithelioid cell melanoma patients compared to spindle shaped melanoma patients and miR-132-3p, conversely, were significantly down-regulated in serum of epithelioid cell melanoma patients. MiR-21-5p showing the best performance (P<0.0001; AUC=0.980) of them. Both miR-199a-3p and miR-21-5p showed great performance in advanced UM. Significant higher levels of miR-21-5p (P<0.001) were found in serum of metastatic UM patients compared to patients with localized spindle shaped melanoma, and significantly higher levels of miR-199a-3p (P<0.001) were detected in serum of metastatic UM patients compared to healthy controls. Our preliminary data indicate promising diagnostic utility of circulating miR-199a-3p and promising prognostic utility of circulating miR-21-5p in both early and advanced UM patients.